Exploring student satisfaction and acceptance of e-learning technologies in Saudi higher education - Alqahtani, Mohammed Ayid; Alamri, Mahdi Mohammed; Sayaf, Amer Mutrik; Al-Rahmi, Waleed Mugahed (Frontiers in Psychology, 2022)
The purpose of this research is to examine how perceived ease of use (PEU), perceived usefulness (PU), and perceived usefulness (PU) mediate the effects of educational quality (EDQ), social influence (SOI), perceived enjoyment (PE), Students' attitude toward use (ATU), and contentment with using an e-learning system (SSE) in an integrated TAM model (PU). Structural equation modeling (SEM) and route analysis were used to evaluate the research model using data from e-learning consumers acquired through a questionnaire. Among the attendees were e-learning users from two major institutions. According to the statistics, EDQ, SOI, and PE all had favorable effects on PEU and PU, as well as students' ATU and satisfaction with the e-learning system. In previous research on e-learning in underdeveloped nations, an integrated strategy was rarely considered. Furthermore, the goal of this study is to look at current works in the field of e-learning systems.